Exorcism and Enlightenment : Johann Joseph Gassner and the demons of eighteenth-century Germany / H.C. Erik Midelfort. - Midelfort, H. C. Erik. (Terry lectures., 2005)
[Publisher-supplied data] In the late eighteenth century, Catholic priest Johann Joseph Gassner (1727-1779) discovered that he had extraordinary powers of exorcism. Deciding that demons were responsible for most human ailments, he healed thousands, rich and poor, Protestant and Catholic. In this book H. C. Erik Midelfort delves deeply into records of the time to explore Gassner's remarkable exorcising campaign, chronicle the official efforts to curb him, and reconstruct the sufferings of the afflicted. Gassner's activities triggered a Catholic religious revival as well as a noisy skeptical reaction. In response to those who doubted that he was really casting out demons, Gassner marshaled hundreds of eyewitness reports that seemed to prove his exorcisms really worked. Midelfort describes the enormous public controversy that resulted, and he demonstrates that the Gassner episode yields important insights into the German Enlightenment and Counter-Enlightenment, the limitations of eighteenth-century debate, and the ongoing role of magic and belief in an age of scientific enlightenment.